Odlingsgränsens påverkan på samhällsomvandlingen i Malmfälten - van der Geer, Lotta (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2024)
This essay investigates how the transformation of society in Malmfälten is affected by thecultivation limit. The essay´s time frame is 2014 and 2018, respectively, because those are thetwo years the comprehensive plans were adopted. The investigation´s approach to answeringthe questions is to analyze the comprehensive plans, as well as study the legislation regardingthe cultivation limit and see if it applies to the documents. Furthermore, the study investigateswhether the cultivation limit has a limiting effect on the social transformation in Kiruna or not.What the investigation came to is that the cultivation limit limits the availability of land and thepossibility to farm the land mainly because of the reindeer husbandry law, which affects theland above the cultivation limit to a large extent, as well as the soil weathering process. Thestudy also concluded that the influence of the cultivation boundary has its advantages, amongother things through the protective effect it gives Sami villages in the area. The theoreticalframework the study relates to is path dependence, which deals with how a historicalphenomenon, such as the cultivation limit with its 150 years behind it, affects the present.